Nutrient Optimization And Computerized Decision Support Program In Recirculating Integrated Aquaculture System - Bakhsh, Hamid Khoda (2005)

(untitled)
There are many research activities to improve sustainable aquaculture and agriculture production in the wide world. Sustainable aquaculture is referred to as production of aquatic commodities through farming activities with social, economic and environmental sustainability. A series of experiments were conducted to compare different inorganic and organic fertilizers to improve production of Macrobrachium rosenbergii and to make a decision support program in an artificial sustainable aquaculture-agriculture system. Simply, nutrient wastes from culture tanks were used to fertilize hydroponics or terrestrial plants production via irrigation water. The sustainability and success functioning of the whole system were involved to manage and optimize the use of supplemented minerals, diet and desirable environment for each compartment (prawn, plant and microorganisms).The first experiment was made to evaluate the tolerance of M. rosenbergii in different levels of inorganic fertilizer (EC) formulated in nutrient film technique (NFT) vegetable production system. Results of the first experiment indicated that desirable growth rate of M. rosenbergii was obtained using 0.1 to 0.5EC of supplemental liquid fertilizer. High concentration of potassium (117-177 mg l-1), ammonia (0.72-1.05 mg l-1) and copper (0.04-0.06 mg l-1) inhibited the growth rate of M. rosenbergii in integrated culture system. The second experiment was carried out to assess the effects of different nutrient and stocking density on different population of M. rosenbergii in polyculture system. A different range of inorganic and organic fertilizer was used in the polyculture of plant and freshwater prawn species. Overall results indicated that essential concentration of nutrients, source and M. rosenbergii stocking density have played a major role in the effectiveness of suitable range of minerals in integrated production system. The results also demonstrated that 0.5 EC liquid inorganic fertilizer was not suitable to provide optimum nutrients and chicken manure is still an important fertilizer even in indoor integrated culture system. Finally, a comparative study was conducted to evaluate the optimum level of chicken manure and formulated inorganic nutrients in an artificial integrated culture system. The results indicated that high density culture of M. rosenbergii juveniles (380-400 individual m-2) in fiberglass tanks is possible by the installation of artificial substrate and controlling of nutrient concentration in system. Moreover the addition of aeration tank significantly improved the quality of water (DO and pH) and freshwater prawn growth (1343.0 g/tank) in recirculated polyculture system. The application of 70 g m-3 chicken manure alone encouraged growth of benthic and periphyton algae in culture tanks. The overall observation illustrated the desirable combination of supplemental liquid fertilizer and chicken manure is essential to obtain best growth for each compartment in sustainable polyculture system. A visual expert program (IAAS) was adopted to improve managing and develop technical operation in an artificial integrated culture system. The operation of the polyculture system required the specific knowledge, developing and application of computer systems to excellent operation, control of water quality variables, dissolved nutrients and feed to avoid the production of toxic substance and increase self efficiency and sustainability of the culture system. The accuracy of IAAS expert program was evaluated by polynomial and linear regression techniques through additional experiment. The comparison of results (yield and survival) in expert and real culture system represents higher variation of survival, prawn and plant yields in abnormal culture system. Moreover the evaluation processes demonstrated succeed performance of IAAS expert program in prediction results of optimized integrated culture system (with low variation). In aquaculture, the success estimation of production depends largely on the state of physical and chemical parameters which define optimal culture conditions.